2018
DOI: 10.1007/s00204-018-2235-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptomics and metabolomics reveal signatures of lipid metabolism dysregulation in HepaRG liver cells exposed to PCB 126

Abstract: Chemical pollutant exposure is a risk factor contributing to the growing epidemic of non-alcoholic fatty liver disease (NAFLD) affecting human populations that consume a western diet. Although it is recognized that intoxication by chemical pollutants can lead to NAFLD, there is limited information available regarding the mechanism by which typical environmental levels of exposure can contribute to the onset of this disease. Here, we describe the alterations in gene expression profiles and metabolite levels in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…In numerous studies, small changes in the physiological processes of cellular metabolism, as observed in accessible biofluids (e.g., blood and urine), have been assigned to a specific toxicological mode of action. In particular, it has been shown that plasma metabolite changes in amino acids, lipids, and bile acids, which may be indicative of liver toxicity induced by various drugs in animal studies, have greater potential for human translation (Beger et al 2015;Iruzubieta et al 2015;Mesnage et al 2018;Sun et al 2014;van Ravenzwaay et al 2007). Several studies have reported that elevated levels of fatty acids, acylcarnitines, and medium chain fatty acids in the serum could be potential markers of liver injury induced by APAP, although they have yet to be demonstrated as satisfactory indicators of injury progression (Chen et al 2009;Coen et al 2003;Kumar et al 2012;Luo et al 2014;Yamazaki et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In numerous studies, small changes in the physiological processes of cellular metabolism, as observed in accessible biofluids (e.g., blood and urine), have been assigned to a specific toxicological mode of action. In particular, it has been shown that plasma metabolite changes in amino acids, lipids, and bile acids, which may be indicative of liver toxicity induced by various drugs in animal studies, have greater potential for human translation (Beger et al 2015;Iruzubieta et al 2015;Mesnage et al 2018;Sun et al 2014;van Ravenzwaay et al 2007). Several studies have reported that elevated levels of fatty acids, acylcarnitines, and medium chain fatty acids in the serum could be potential markers of liver injury induced by APAP, although they have yet to be demonstrated as satisfactory indicators of injury progression (Chen et al 2009;Coen et al 2003;Kumar et al 2012;Luo et al 2014;Yamazaki et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolome data analysis was performed using MetaboAnalyst 4.0 (Chong et al 2018). Peak area values were median scaled, log transformed, and any missing values imputed with sample set minimums, both on a per biochemical basis as previously described (Mesnage et al 2018). Log-transformed data was analysed using an ANOVA test adjusted for multiple comparisons with Fisher's least significant difference in order to determine if there was a difference in mean value between the different treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…The scan range varied slightly between methods but covered 70-1000 m/z. Raw data was extracted, peak-identified and QC processed using Metabolon's hardware and software as previously described (Mesnage et al 2018).…”
Section: Metabolomics Analysismentioning
confidence: 99%
“…The main route of exposure to PCBs is the consumption of contaminated foods such as fish and shellfish. PCBs have been related to hormone-dependent cancers, an impaired reproductive system, and cognitive and metabolic disorders (such as impaired glucose metabolism and adipocyte inflammation) [107,108].…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%